Investigation into skin physiological parameters and mocroflora characteristics of melasma population in Lhasa China - Fang, Longwei; Luo, Bu; Danzen, Deqiong; Yang, La; Gao, Yun; Ni, Zhen; Wang, Jin; Duoji, Zhuoma; Ci, Yang; Suolang, Wangdui; Ge, Wang; Basang, Zhuoma (Frontiers in Microbiology, 2026)
Melasma is a skin disease characterized by symmetrical pigmentation, mainly occurring in the exposed areas of the face, which has some relationship with skin parameters and bacterial diversity. High-altitude regions experience elevated ultraviolet (UV) radiation, potentially influencing skin parameters and microbial characteristics in melasma. To explore the inherent law of the melasma mechanism in high altitude, the hereditary Tibetans at high altitude in Lhasa, Tibet were investigated. Skin physiological parameters such as skin sebum (SM), corneum moisture content (CM), pH, trans epidermal water loss (TEWL), skin erythema index (E), melanin (M), individual typology angle (ITA) and so on, were measured and the microbiome characteristics were sequenced and analyzed. The results showed that among 302 participants, 36 were diagnosed with melasma (mean prevalence: 11.92%). Prevalence was significantly higher in females (16.67%) than males (2.04%), peaking in females aged 31–40 years (37.50%). Melasma patients exhibited significantly lower pH and higher M values compared to controls (p < 0.05). Community diversity analysis of alpha and beta of skin bacteria and fungi showed that the abundance, diversity, and flora composition in melasma population were basically the same as that of control population (p > 0.05). Species analysis of intergroup differences showed that the bacteria were dominated by the genera of Cutibacterium, Staphylococcus and so on, but it was no statistical significance, while Malassezia. Aspergillus, Aureobasidium, and Penicillium were the dominant genera of fungi at the genus level, with Aspergillus and Aureobasidium larger in the melasma group than the control group (p < 0.05). Correlation analysis showed that there were significant differences between the flora characteristics and the parameters of ITA, TEWL, pH, and E, M, SM, which may has the association with the formation of melasma. The ROC analysis assessing fungi such as Aspergillus, Aureobasidium as a predictor of melasma yielded an AUC of 0.798, 0.828, indicating fair discriminatory ability. These findings demonstrate that high altitude hereditary Tibetan melasma population in Tibet has diverse skin parameters and microflora structural features. The strong correlation between microflora characteristics, skin parameters, and melasma prevalence provides a new foundation for research on the prediction, prevention, and treatment of dermatological conditions in high-altitude populations.